DELIVERING SERVICE CONVENIENCE TO ENHANCE CUSTOMER SATISFACTION: QUANTITATIVE ANALYSYS ON SHOPEE - Daud, Renny O.; Tulung, Joy E.; Gunawan, Emilia M. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: Electronic commerce, commonly known as e-commerce or e-shopping, consists of the buying and selling of goods or services over electronic systems such as Internet.One of the biggest e-commerce in Indonesia is shopee. To remain the best in this field, and not less competitive with other e-commerce, in order to maintain loyal customers, shopee has to concern about the customer satisfaction. The purpose of this study is to find out more about the influence of service convenience to increase customer satisfaction on shopee platform. Four variables used in this research, are access convenience, search convenience, transaction convenience and post-purchase convenience. This study employs multilinear regression to investigate the influence of those variables to enhance customer satisfaction. This study conducts with 100 shopee’s customer in Manado as the respondents. Findings of this research show that search convenience, transaction convenience and post-purchase convenience significantly influence customer satisfaction when they use shopee application. Meanwhile access convenience cannot increase shopee’s customer satisfaction. In order to increase and maintain customer satisfaction, shopee has to improve the quality of the application to make the customer more feel comfort when they used shopee.Keywords: service convenience, access convenience, search convenience, transaction convenience post-purchase convenience, customer satisfaction, e-commerce.